2010
DOI: 10.1126/science.328.5984.1344
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Kon-Tiki : Did Polynesians Sail to South America?

Abstract: After decades of taboo and controversy, Pacific Rim archaeologists are finding new evidence that Polynesians reached South America before Europeans did, voyaging across the world's largest ocean around 1200 C.E.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…Significantly, genetic evidence for kumara lineage sweet potato in eastern Polynesia supports other evidence for pre-European contacts between Polynesia and western South America (15). Parsimony suggests Polynesian, rather than South American, voyagers as the prime movers, given that Polynesians colonized remote archipelagos and islands throughout the vast Pacific Ocean.…”
Section: Broader Implicationssupporting
confidence: 56%
“…Significantly, genetic evidence for kumara lineage sweet potato in eastern Polynesia supports other evidence for pre-European contacts between Polynesia and western South America (15). Parsimony suggests Polynesian, rather than South American, voyagers as the prime movers, given that Polynesians colonized remote archipelagos and islands throughout the vast Pacific Ocean.…”
Section: Broader Implicationssupporting
confidence: 56%
“…However, Tiwanaku and Easter Island cultures similarities are more significant than genetic coincidences, also more cultural traits are common (Green, 2000;Lawler, 2010;Storey et al, 2007;Storey et al, 2008;Wallin et al, 2005). Ancient gene flow between both Aymara people and Easter Islanders may have been diluted with time and in this particular case may be as useful as cultural shared traits, at present.…”
Section: Aymaras and Easter Islandersmentioning
confidence: 99%
“…Recent genetic studies have identified Polynesian mtDNA haplogroups in remains (skulls) of Botocudo Amerindians from Brazil (Amerindian group extinct by the end of 19th century) (Goncalves et al, 2013). Other signs may indicate a communication between these groups of populations, like the presence of South American sweet potato in earlier Pacific sites (Lawler, 2010) or the finding of chicken remains of Polynesian type in El Arenal (Chile) dated by radiocarbon back to 1300-1400 AD (Storey et al, 2007;Storey et al, 2008). Furthermore, skeletal remains of pre-Columbian individuals with Polynesian ancestry and several Mapuche artefacts which are similar to Polynesian ones at Mocha island (Chile) have been recently reported (Lawler, 2010;Matisoo-Smith & Ramirez, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, there is strong evidence that Polynesians had been in South America early, i.e. in pre-Columbian time (see also Lawler [33]). After having arrived in South America, some of them may have returned to Polynesia, including Easter Island, not only taking the sweet potato and bottle gourd, etc., but also some native Americans with them.…”
Section: How Did the Early Amerindians Reach Easter Island?mentioning
confidence: 99%